Structural basis for ligand capture and release by the endocytic receptor ApoER2. (26th April 2017) - Hirai, Hidenori; Yasui, Norihisa; Yamashita, Keitaro; Tabata, Sanae; Yamamoto, Masaki; Takagi, Junichi; Nogi, Terukazu
Abstract: Apolipoprotein E receptor 2 (ApoER2) is a close homologue of low‐density lipoprotein receptor (LDLR) that mediates the endocytosis of ligands, including LDL particles. LDLR family members have been presumed to explore a large conformational space to capture ligands in the extended conformation at the cell surface. Ligands are subsequently released through a pH‐titrated structural transition to a self‐docked, contracted‐closed conformation. In addition to lipoprotein uptake, ApoER2 is implicated in signal transduction during brain development through capture of the extracellular protein reelin. From crystallographic analysis, we determine that the full‐length ApoER2 ectodomain adopts an intermediate contracted‐open conformation when complexed with the signaling‐competent reelin fragment, and we identify a previously unappreciated auxiliary low‐affinity binding interface. Based on mutational analyses, we propose that the pH shift during endocytosis weakens the affinity of the auxiliary interface and destabilizes the ligand–receptor complex. Furthermore, this study elucidates that the contracted‐open conformation of ligand‐bound ApoER2 at neutral pH resembles the contracted‐closed conformation of ligand‐unbound LDLR at acidic pH in a manner suggestive of being primed for ligand release even prior to internalization. Synopsis: ApoER2 is a close homologue of the LDL receptor. The crystal structure of the ApoER2 ectodomain in complex with the signaling‐competent fragment of reelin serves as a representative model for the pH‐dependent ligand uptake mechanism conserved within the LDLR family. The structure of the ApoER2 ectodomain in complex with its physiological ligand has been determined by X‐ray crystallography. The LA2 module of ApoER2 serves as a low‐affinity auxiliary interface for reelin and is expected to modulate ligand‐receptor interactions during endocytosis. The conformation of ligand‐bound ApoER2 resembles that of the closed state of LDLR at acidic pH rather than that of the extended state at neutral pH, indicating that ApoER2 is primed for ligand release even before internalization. Abstract : The crystal structure of the ApoER2 ectodomain in complex with reelin serves as a representative model for the pH‐dependent ligand uptake mechanism conserved within the LDLR family.